Apical extrusion of debris and irrigants using different irrigation needles - Silva, Paula Barcellos; Krolow, Angélica Mohnsam; Pilownic, Katerine Jahnecke; Casarin, Renata Picanço; Lima, Regina Karla Pontes [UNESP]; Leonardo, Renato de Toledo [UNESP]; Pappen, Fernanda Geraldo (FapUNIFESP (SciELO), 2016)
This study evaluated the influence of irrigation tip, root canal curvature and final apical diameter on periapical debris and irrigant extrusion during root canal instrumentation. After being classified as mildly or moderately curved, the mesiobuccal root canals of 90 human molars were instrumented. The teeth were allocated into three groups according to the used needle type: a flat open-end needle (Group 1), a side-vented needle (Group 2) or a double side-vented needle (Group 3). The amount of extruded material after instrumentation was calculated for each group. The differences in irrigant and debris extrusion between the experimental groups were analyzed with the Mann-Whitney U test. Irrigation tips and final instrument diameter differences were analyzed with the Kruskal-Wallis test. Multiple groups were compared using the Mann-Whitney U-test with a Bonferroni correction at α=0.05. The amount of extruded material from the double side-vented needle was significantly less than the open-ended flat needle (p=0.008), but there was no difference compared to the side-vented needle (p=0.929). The results showed no effect of root curvature and final apical diameter on the amount of irrigant and debris extrusion (p>0.05). The double side-vented needles generated the least material extrusion to the periapical tissues. Irrigation needle type had the greatest influence on periapical irrigant and debris extrusion and the double side-vented needles may be safely used during endodontic therapy.
Keywords: Apical extrusion; Endodontics; Irrigation; Irrigation needle